Factors determining mortality in sepsis: An analysis of clinical and epidemiological aspects - Sousa, Rute Vieira de (2024)
The general objective of this study is to analyze the determining factors of mortality in sepsis, considering clinical and epidemiological aspects. To achieve this, the specific objectives include: identifying the demographic characteristics of patients with sepsis, understanding the role of the nurse in caring for critically ill patients with sepsis, and evaluating the relationship between comorbidities and the severity of sepsis. This study is justified as it addresses one of the leading causes of mortality in the hospital setting, particularly in Intensive Care Units. By elucidating the clinical and epidemiological aspects that influence mortality, the work contributes to the promotion of equity in access to appropriate healthcare. This is an integrative literature review. The search was conducted online through articles indexed in the electronic databases SCIELO, LILACS, and MEDLINE. The following search terms were used: sepsis; intensive care unit; comorbidities. The results highlight that the severity of sepsis is closely related to demographic characteristics such as age and comorbidities, as well as care-related factors like early identification and appropriate treatment. These findings reinforce the importance of targeted interventions aimed at improving the detection and management of sepsis, especially in more vulnerable populations.